First year student conceptions of success : What really matters? - Naylor, Ryan (Student Success v.8 n.2 p.9-19 https://doi.org/10.5204/ssj.v8i2.377, 2017)
Success at university is a complex idea, with evidence that what 'counts' as success is conceived differently by students and academics. This study contrasts two methodologies ('Likert-type' ordered response and quadratic voting, which does not appear to have been applied to education research previously) to identify which factors are important in university success to first year health science students. Completion (passing subjects and obtaining qualifications) and achievement (getting good grades) were the most important factors in both methodologies, but important differences were found between the two in the relative importance of four factors, particularly in the importance of a sense of belonging and personalisation of study options. Contrasting data from the two methods potentially separates factors students think are vital from those that are important but not essential-a distinction which is concealed using Likert-type instruments alone. [Author abstract]